2000
DOI: 10.1063/1.1309033
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced microbending losses in double-coated optical fibers during temperature cycling

Abstract: The thermally induced microbending losses in double-coated optical fibers during temperature cycling are analyzed. The compressive radial stress at the interface between the glass fiber and primary coating would produce the microbending loss. A simplified closed-form formula to calculate the microbending loss is obtained by the viscoelastic theory. This formula can be extended to calculate microbending losses induced by temperature cycling with any number of stages, if the temperature is linearly raised, linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Moreover, A 0 and A 2 represent the crosssectional areas of the glass fiber and the secondary coating, respectively. 9,17,[20][21][22][23][24] Accordingly, the long-term stresses in optical fibers can be solved by the viscoelastic theory, as follows. Although the approach stated here is less rigorous than the exact theory-of-elasticity treatment, 18 it often enables easy to use and sufficient accurate solutions to be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, A 0 and A 2 represent the crosssectional areas of the glass fiber and the secondary coating, respectively. 9,17,[20][21][22][23][24] Accordingly, the long-term stresses in optical fibers can be solved by the viscoelastic theory, as follows. Although the approach stated here is less rigorous than the exact theory-of-elasticity treatment, 18 it often enables easy to use and sufficient accurate solutions to be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Although the viscoelastic behavior of polymeric coatings is not very clear, polymeric coatings can be simply and reasonably assumed to behave as Maxwell materials. 5,6,9 As a result, long-term stresses in glass fibers can be determined from the viscoelastic theory as follows. 10 First, the Young's modulus of the polymeric coating, given in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Although the glass fiber behaves like an elastic medium, polymeric coatings for optical fibers are typically viscoelastic materials. As a result, the stresses exerted on the coating are relaxed, 5,6 and the applied tensile force is gradually transferred from the polymeric coatings to the silica glass fiber over a long time. Equation ͑1͒ shows that increasing the tensile stress, a , applied to the glass fiber accelerates the failure of the glass fiber over a long period.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal or mechanical stresses in optical fibres are important, and have been extensively studied [1–10]. Suhir [11] first paid attention to thermally induced stresses in single‐coated optical fibres at low temperatures, and found that added transmission losses increased with the lateral pressure on the glass fibre.…”
Section: Introductionmentioning
confidence: 99%